IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH MACROMEDIA FLASH APPLICATION IN THE THEME OF “KAYANYA NEGERIKU” AT GRADE IV SD BINTANG TIMUR RANTAUPRAPAT - Lusia Dorisma Sinaga; Dewi Anzelina; Anton Sitepu (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aimed to improve students’ learning outcomes through the implementation of macromedia flash application on the theme of “Kayanya Negeriku” at SD RK Bintang Timur Rantauprapat. This research was Classroom Action Research. The subjects of this research were 30 students at grade IV consisting of 17 male students and 13 female students. This research was conducted in two cycles with two meetings in each cycle. The research data were obtained from tests and observations. The results showed an increase on students’ learning outcomes after the implementation of Macromedia Flash application. This was proved by the increase of students’ learning outcomes in each cycle. The results in the pre-test showed that 7 students (23%) reached the learning mastery while 23 students (77%) did not yet reach the learning mastery with the average score of 57.33 then, in cycle 1, 13 students (43%) were completed the learning mastery while 17 students (57%) did not reach the learning mastery with the average score of 73.00. Moreover, in the second cycle 24 students (80%) reached the learning mastery while 6 students (20%) did not with the average score of 83.00. The results of observations in cycle I found that 64% of teachers got sufficient category and 62% of students also got sufficient category. Then, the results in cycle II, the observation for teachers increased to 82% with very good category while the observation for students increased to 84% with good category. Based on the percentage of learning outcomes and observations, it can be concluded that implementing Macromedia Flash application improved students’ learning outcomes.